The Structure of Space and Problems of Our Time - Светлана Головня; Константин Лидин (Проект Байкал)
Since antiquity the image of space as emptiness has been opposed to the image of material space filled with some essence. For a long time this role was played by the theories of ether. During the twentieth century, a model of space filled with metrics, i.e., information, was formed in physics. Since the middle of the last century, the social and psychological sciences have rapidly developed models which treat space as a structured continuum. Many phenomena of quantum and relativistic theory look quite adequate in the sphere of humanities, particularly in the history and theory of architecture. It is shown how the model of structured space can be used to understand architectural and urban planning problems of our time.